Integration of Circular Economy and CSR for Sustainable Innovation in Business - Wany, Eva; Supriadi, Iman; Prayitno, Budi; Yuliarini, Sarah (Proceedings of International Conference of Graduate School on Sustainability, 2025)
This study aims to explore the integration between the circular economy and corporate social responsibility (CSR) within sustainable business practices. The primary focus of this research is to understand the role of CSR in driving sustainable innovation through the implementation of circular economy models and its impact on company profitability and social value. This research employs a qualitative method using a case study and literature review approach. The case study is drawn from global companies that have successfully implemented the circular economy and CSR synergistically, while an in-depth literature review is used to analyze the theories and concepts underlying the relationship between these two approaches. Data were collected from annual reports, sustainability reports, and other supporting documents. The findings reveal that companies that successfully integrate the circular economy with CSR experience increased operational efficiency and enhanced social reputation. Moreover, this synergy also promotes sustainable innovation, which positively affects company profitability. Other positive social impacts include waste reduction and significant contributions to community development. The study contributes theoretically by strengthening the relationship between CSR and sustainable innovation within the framework of the circular economy. Practically, this research provides guidance for companies seeking to adopt more sustainable business models, demonstrating the economic and social benefits generated from this synergy.